Hubungan Penerapan Sistem Informasi Pendokumentasian Asuhan Keperawatan Dengan Kepuasan Perawat Di Rumah Sakit Wilayah Jakarta - Roganda Situmorang (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2022)
Nurses are a profession in health facilities with the largest number of health workers and have a high workload as evidenced by the documentation of nursing care. Nurses report dissatisfaction with documentation that has not been integrated into an information system in the form of complaints or problems and tired of documenting as proof of their performance. The study aims to determine the relationship between the implementation of a nursing care documentation information system and nurse satisfaction at the Jakarta Regional Hospital. The research method used quantitative research with a descriptive correlation type with a cross sectional approach to the population of nurses implementing inpatient rooms and using a total sampling technique. The research sample is 60 nurses. Retrieval of data using observation sheets for the application of nursing care documentation information systems and questionnaires for nurse satisfaction. The data were then analyzed with the chi square test. The results showed that there was a significant relationship (p) = 0.000 between the implementation of the nursing care documentation information system and nurse satisfaction. The more optimal the implementation of the nursing care documentation information system, the better the nurse's satisfaction. The recommendation from the results of this study is that hospitals can provide video links for nurses containing socialization or dissemination of information systems that are used as learning materials as well as implementation and provide information system infrastructure facilities such as computers according to the number of existing nurses or development that can be accessed via mobile phones.